Networks of the Ulama in the Haramayn: Connections in the Indian Ocean Region - Azyumardi Azra (Studia Islamika, 2001)
The involvement of the ulama of the Indian Ocean region took at least two forms. Firstly, through their travelling or migrating to the Holy Cities of Mecca and Medina (the Haramayn). The author found that a great number of ulama and students from the Indian Ocean region came to and later settled in the Holy Cities to study and teach. Secondly, students who felt that they possessed sufficient knowledge returned to their place of origin in the Indian Ocean region, teaching and forming networks of ulama and students in their own area. As a consequence, through these two methods, there appeared a complex criss-crossing of networks of ulama in the Indian Ocean region and other areas of the Muslim world.DOI: 10.15408/sdi.v8i2.689